A BRIEF HISTORICAL SURVEY OF TRANSLATION THEORIES AND THEIR CONTRIBUTION TO A PRACTICAL ORIENTATION OF THE DISCIPLINE - AKPACA, SERVAIS MARTIAL (My University, 2019)
Eric Jacobsen claims in Translation, A Traditional Craft (1958) that translation is a Roman invention. No matter whether this statement is true or not, the Roman translators Cicero and Horace were the first to write translation theories that influenced subsequent generations of translators for centuries. They advocated literal as well as free translation. The aim of this paper is to show that the various translation theories developed by authors such as St. Jerome, Richard Rolle, Etienne Dolet, George Chapman, Walter Benjamin and Eugene Nida oriented the practise of this activity in religious and secular circles. The methodology of the paper is mostly descriptive and analytic in the sense that an effort is made to identify several translation theories and to analyse their content and contribution to the practise of the discipline over the years. The result of this investigation is that translation is a great source of language enrichment and inter-lingual communication as well as a channel through which several transactions take place, including coinage, popularisation of foreign cultures and literary traditions, comparative stylistics, research in terminology and rhetoric.
Keywords: Translation theories; history; linguistics; culture; science